Participatory Communication Strategy of the Village Head in Increasing Community Involvement in Cikumbueun Village - Hilal, Samsu (EQUATOR SINAR AKADEMIA, 2025)
Communication is a vital tool for conveying intentions and coordinating actions. In village governance, effective communication enables the village head to share vital information with the community. This study explores how the head of Cikumbueun Village in Pandeglang Regency, Banten, implements communication strategies during development initiatives. It also examines supportive and inhibiting factors that influence the strategy’s effectiveness. Utilizing qualitative descriptive methods and purposive sampling, data were gathered through observation and interviews.The village head adopts a participatory communication strategy, which includes community-wide meetings (musyawarah desa) and grassroots discussions. This approach has proven effective in relaying information and fostering engagement. However, several challenges impede full impact: residents’ limited availability, generational disparities in participation, and occasional misunderstandings in verbal communication. These obstacles highlight the need for adaptive methods—such as flexible scheduling, inclusive outreach, and clearer messaging—to enhance the community’s involvement in development efforts.